Pengaruh Pelibatan Pemangku Kepentingan dan Tanggung Jawab Sosial Pada Reputasi Perusahaan - Ni Putu Manik Julythiawati; Putu Agus Ardiana (Public Service and Governance Journal, 2023)
The purchasing power of the community continues to increase towards food and beverage products, leading to the active production of companies in the food and beverage industry. Some companies pay attention to their social responsibility towards the surrounding environment. Therefore, by involving stakeholders and disclosing Corporate Social Responsibility (CSR) in company operations, it can help address damage to the company's image. The aim of this research is to determine the influence of stakeholder engagement practices and CSR activity disclosure on corporate reputation. The sampling method used in this study is purposive sampling, with a total of 38 observations. The research findings indicate that stakeholder engagement and the disclosure of corporate social responsibility have a positive and significant impact on corporate reputation. The implication of this research is to provide input to company management to consistently disclose CSR activities and involve stakeholders inclusively.